2016
DOI: 10.1186/s12875-016-0547-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices towards antibiotic use in upper respiratory tract infections among patients seeking primary health care in Singapore

Abstract: BackgroundPatients’ expectations can influence antibiotic prescription by primary healthcare physicians. We assessed knowledge, attitude and practices towards antibiotic use for upper respiratory tract infections (URTIs), and whether knowledge is associated with increased expectations for antibiotics among patients visiting primary healthcare services in Singapore.MethodsData was collected through a cross-sectional interviewer-assisted survey of patients aged ≥21 years waiting to see primary healthcare practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 25 publications
5
58
1
2
Order By: Relevance
“…There were also reports suggesting a lack of awareness of AMR from the public and as a result, patients continued demanding antibiotics even when they were not clinically indicated. This was also reported in a Singaporean study that surveyed patients and found that most patients seeking primary health care in Singapore were misinformed about the role of antibiotics, with poor knowledge being associated with wanting antibiotics [32].…”
Section: Discussionmentioning
confidence: 52%
“…There were also reports suggesting a lack of awareness of AMR from the public and as a result, patients continued demanding antibiotics even when they were not clinically indicated. This was also reported in a Singaporean study that surveyed patients and found that most patients seeking primary health care in Singapore were misinformed about the role of antibiotics, with poor knowledge being associated with wanting antibiotics [32].…”
Section: Discussionmentioning
confidence: 52%
“…There remains a gap in knowledge about the amount and appropriateness of antibiotic prescribing in the primary healthcare setting in Singapore, although it is likely that improvements can be made. (53) A similar gap exists for antibiotics prescribed in local veterinary and agricultural practices. In these settings, in addition to attempts to improve data capture, strategies to improve prescribing practices in the community -such as guidelines for antibiotic prescription and incentives to encourage proper antibiotic usage -should be developed to tackle the issue of inappropriate prescribing.…”
Section: Community and Veterinary Prescription Of Antibioticsmentioning
confidence: 98%
“…As misconceptions about appropriate antibiotic use and the consequences of misusing antibiotics are common, (53) education is needed to guide people towards a correct, unified understanding and perception of AMR, including its impact on society. Education serves two main purposes: (a) to let the target audience recognise that AMR is an urgent issue that needs to be acted upon; and (b) to equip them with the right knowledge to effectively participate in activities against AMR.…”
Section: Education On Antimicrobial Resistance and Antibiotic Prescrimentioning
confidence: 99%
See 1 more Smart Citation
“…Despite URTIs generally being minor illnesses, they result in an appreciable number of medical consultations globally 87,[199][200][201][202][203] . The number of healthcare consultations combined with parental and patient pressure increases antibiotic use for URTIs including LMICs thereby increasing AMR rates 88,153,200,[204][205][206][207][208][209] . Patients or parents who are concerned about their or their child's respiratory illness are likely to seek treatment, and want an antibiotic, especially if they perceive the illness as severe 21,209,210 .…”
Section: Aetiology Of Urtis and Symptomsmentioning
confidence: 99%